Adolescent non-suicidal self-injury and its relationships with school bullying and peer rejection. (April 2019) - Esposito, Concetta; Bacchini, Dario; Affuso, Gaetana
Highlights: Peer dynamics as precursors of NSSI have become an important field of research. Bullying involvement is a relevant factor risk for NSSI engagement. Peer rejection amplifies the risk for NSSI only in victims and bully-victims. Abstract: The central goal of this study was to examine the associations of school bullying and peer rejection with non-suicidal self-injury (NSSI), as well as their interactive role in a sample of non-clinical adolescents. Six hundred and forty adolescents (253 Males, M age  = 15.60, SD  = 1.65) self-reported measures of school bullying and NSSI and provided sociometric ratings of peer rejection. The results showed that being involved in bullying (as bullies, victims, or bully-victims) increases the likelihood to engage in NSSI; being rejected by peers amplifies the probability, for victims and bully-victims, of using NSSI at least once. The findings support the hypothesis that peer relationships play a key-role in determining NSSI and the importance to implement programs aimed to improve the school climate in order to avoid maladjusted behaviors in adolescence.